2020
DOI: 10.1097/pcc.0000000000002337
|View full text |Cite
|
Sign up to set email alerts
|

Profile of Fluid Exposure and Recognition of Fluid Overload in Critically Ill Children

Abstract: Objectives: Fluid overload is common in the PICU and has been associated with increased morbidity and mortality. It remains unclear whether fluid overload is a surrogate marker for severity of illness and need for increased support, an iatrogenic modifiable risk factor, or a sign of oliguria. The proportions of various fluid intake contributing to fluid overload and its recognition have not been adequately examined. We aimed to: 1) describe the types and amounts of fluid exposure in the PICU and 2)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 32 publications
0
32
0
Order By: Relevance
“…The median length of hospital stay of all the included patients was 17 days (IQR 9-34). The group receiving hypotonic solutions had a longer stay (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38) than the group receiving isotonic solutions (14 days IQR 8-30) (p = 0.000). The use of hypotonic solutions was associated with 8 more days of total hospital stay (difference in means 8, 95% CI 2.67, 13.3, p = 0.001) (Figure 2A).…”
Section: Resultsmentioning
confidence: 99%
“…The median length of hospital stay of all the included patients was 17 days (IQR 9-34). The group receiving hypotonic solutions had a longer stay (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38) than the group receiving isotonic solutions (14 days IQR 8-30) (p = 0.000). The use of hypotonic solutions was associated with 8 more days of total hospital stay (difference in means 8, 95% CI 2.67, 13.3, p = 0.001) (Figure 2A).…”
Section: Resultsmentioning
confidence: 99%
“…Pediatric studies, although smaller in size, have demonstrated a similar trend in the volume burden associated with maintenance fluids. 14,15 Maintenance fluids are primarily used to prevent dehydration and to provide a source of glucose to prevent starvation ketosis. However, our data demonstrate that maintenance fluids are frequently given to patients with fluid in excess of hydration requirements and this practice may represent iatrogenic harm.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in children have also demonstrated that a large fluid burden may result from non-resuscitation fluids, especially maintenance fluids. 14,15 Recently, Al-Lawati et al 15 demonstrated that fluid exposure frequently exceeded hydration requirements on day 3 of pediatric intensive care unit (PICU) admission. However, the degree to which non-resuscitation fluid in excess of hydration requirements impacts clinical outcomes has not been previously studied.…”
Section: Introductionmentioning
confidence: 99%
“…Remarkably, the sheep receiving fluid boluses had a higher need of vasopressor support, indicating only a temporary effect of fluid resuscitation. Nevertheless, this study does not report on fluid maintenance therapy, which also significantly impacts hemodynamic response and fluid accumulation (14,15). Indeed, a recent clinical study shows that the timing of peak fluid overload is an important indicator of adverse outcome (8).…”
Section: Hemodynamic Resuscitationmentioning
confidence: 92%
“…Besides fluid loading during the resuscitation phase, ongoing intravenous fluid administration during the maintenance phase strongly contributes to fluid overload (14,15). As such, early fluid restriction in both resuscitation practice and in the maintenance phase of (P)ARDS may prove beneficial.…”
Section: Introductionmentioning
confidence: 99%